(untitled) (Orchid Insights: A Multidisciplinary Journal of Orchid College, 2025)
The core of image processing lies from the principal to represent the digital image in signals of 2-3 dimensions and applying the techniques of digital signal processing to obtain the diverse parameters related to image. Edge detection is the preprocessing techniques of image processing which includes mathematical methods that aims in identifying the sharp discontinuities in an image. The theme of this article is particularized on the performance analysis among Canny Edge Detection and Laplacian of Gaussian (LoG) Edge Detection algorithms on behalf of their execution time. The result in this study shows that the performance of LoG Edge detection algorithm is better than the performance of Canny Edge detection algorithm on the basis of their execution time.